1997
DOI: 10.1149/1.1837608
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Bonding of GaAs Wafers for Nonlinear Optics Applications

Abstract: Diffusion-bonded stacked periodic structures represent a new family of optical materials with spatially patterned nonlinear properties. The bonding process preserves both the optical and mechanical properties of the bulk materials. GaAs devices up to 20 layers were diffusion bonded and characterized. Optical loss was from interfacial voids and gaps at shorter wavelengths and from processing-induced p-type free carrier absorption at longer wavelengths. InfroductionHigh-power laser sources in the mid-infrared (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…One can show that, within the r th grain, the electric field amplitude at frequency 2ω generated by the fundamental field is [21]: The random orientation of the grains implies that the normalized component of the nonlinear polarization in the direction of the incident electric field ranges from 1 to −1. To implement this numerically, we used a random number generation algorithm so that (2) For a given average grain-size, the effect of size-distribution on the conversion efficiency can be best determined using a Monte Carlo simulation [21]. Figure 8 shows the simulation results for a SHG process in polycrystalline ZnSe pumped at a wavelength λ = 4.7 µm at which the coherence length is 100 µm.…”
Section: Effect Of Grain-size Distribution On Shg Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…One can show that, within the r th grain, the electric field amplitude at frequency 2ω generated by the fundamental field is [21]: The random orientation of the grains implies that the normalized component of the nonlinear polarization in the direction of the incident electric field ranges from 1 to −1. To implement this numerically, we used a random number generation algorithm so that (2) For a given average grain-size, the effect of size-distribution on the conversion efficiency can be best determined using a Monte Carlo simulation [21]. Figure 8 shows the simulation results for a SHG process in polycrystalline ZnSe pumped at a wavelength λ = 4.7 µm at which the coherence length is 100 µm.…”
Section: Effect Of Grain-size Distribution On Shg Efficiencymentioning
confidence: 99%
“…Birefringent single-crystals are the most commonly used media for this process, but index dispersion limits their conversion efficiency unless the phase matching conditions are satisfied -by exploiting the birefringence phenomenon through angular orientation and proper temperature tuning. In the past two decades, the development of quasi-phase-matching (QPM) techniques involving periodically-poled, diffusion bonded [1,2] or epitaxially-grown materials, such as periodically-poled LiNbO 3 (PPLN) [3][4][5], orientation-patterned GaAs (OPGaAs) [6,7] or GaP (OPGaP) [8][9][10], have been extensively studied to alleviate this issue. The inversion of the sign of the nonlinear coefficient eliminates destructive interferences and allows the generated intensity to grow quadratically with the sample thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55][56][57] The best way to fabricate stacked-plate is to have crystal plates being diffusion-bonded to each other. Diffusion bonding consists of carefully polishing, cleaning, and placing.…”
Section: Fundamentals Of Opomentioning
confidence: 99%
“…Most recently, Vodopyanov et al demonstrated room temperature terahertz generation in QPM GaAs using femtosecond laser pulses. 5 Early orientation-patterned GaAs (OP-GaAs) was obtained by stacking 2 or wafer bonding 6,7 of GaAs wafers with alternating crystal orientations, resulting in changing the sign of the nonlinear optical coefficient periodically. Wafer fusion bonding of multiple wafers can produce OP crystals with large optical apertures and is attractive for LWIR and terahertz generation.…”
Section: Introductionmentioning
confidence: 99%
“…This freedom in choice of the orientation can be further explored for QPM and integrated device applications. [3][4][5][6][7][8]11 From the refractive index measurements for GaAs at 25°C, 12 the calculated relationships between idler and signal wavelengths (λ) across a range of QPM periods and for three pump wavelengths are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%